Health and toxicity in content moderation: the discursive work of justification - Gibson, Anna D.; Docherty, Niall; Gillespie, Tarleton (Information, Communication & Society, 2023)
Within academia, industry, and government, the terms ‘health’ and ‘toxicity’ are widely used to describe and justify decisions around online content and its removal. However, the meanings of these terms are assumed to be self-evident and therefore are rarely examined. This article turns a critical eye to the health and toxicity metaphor to unpack its hidden political work. We trace the metaphor through three different discourses: the historical political economy of the term, the usage by cultural elites in the last two decades, and finally through its contemporary instrumental usage by volunteer content moderators on Facebook. By linking these discourses together, we argue that the metaphor of health and toxicity serves as a means for justification and legitimacy under contemporary neoliberalized orders that typically chafe at modes of public intervention and the language of democratic statecraft. Rather than elucidating the challenges of online content, we find that the metaphor often serves to obfuscate or sidestep the hardest problems in democratic governance. This analysis therefore has practical significance for researchers, policymakers, journalists, and other speakers that publicly traffic in this discourse at large.